Multi-Faceted Influence of Obesity on Type 1 Diabetes in Children – From Disease Pathogenesis to Complications - Ciężki, Sebastian; Kurpiewska, Emilia; Bossowski, Artur; Głowińska-Olszewska, Barbara (Frontiers in Endocrinology, 2022)
The prevalence of overweight and obesity among youth patients with diabetes type 1 is increasing. It is estimated, that even up to 35% of young patients with this type of diabetes, considered so far to be characteristic for slim figure, are overweight or even obese. General increase of obesity in children’s population complicates differential diagnosis of the type of diabetes in youths. Coexistence of obesity has clinical implications for all stages of diabetes course. It is confirmed, that obesity is the risk factor for autoimmune diabetes, and is connected with the earlier onset of diabetes in predisposed patients. Many diabetic patients with obesity present additional risk factors for macroangiopathy, and are recognised to present metabolic syndrome, insulin resistance, and typical for diabetes type 2 - polycystic ovary syndrome, or non-alcoholic fatty liver disease. The prevalence of obesity rises dramatically in adolescence of diabetic child, more often in girls. It has negative impact on metabolic control, glycaemic variability and insulin demand. The risk for microangiopathic complications increases as well. The treatment is difficult and includes not only insulinotherapy and non-pharmacological trials. Recently treatment of insulin resistance with biguanids, and treatment with typical for type 2 new diabetes drugs like GLP-1 analogs, SGLT-2 receptor inhibitors, or even cases of bariatric surgery also has been reported.